2021
DOI: 10.3389/fcomm.2021.669744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Science Communication: Current Practices, Challenges, and Future Implications

Abstract: Scientifically substantiated evaluations are pivotal to ensuring the effectiveness and improvement of the growing number of science communication projects. Yet current evaluation practices are still lacking in various respects. Based on a systematic review of evaluation reports, an online survey of, as well as discussion rounds with science communication practitioners in the German-speaking countries, we discuss three main challenges of science communication evaluation: (1) There is a conflation of impact goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 14 publications
0
31
0
5
Order By: Relevance
“…The use of online comparative judgement could therefore be used to address issues in the quality of evaluation of science communication and STEM engagement activities identified by other researchers [Jensen, 2014;Ziegler et al, 2021] by providing a clear method of pre-and post-intervention evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of online comparative judgement could therefore be used to address issues in the quality of evaluation of science communication and STEM engagement activities identified by other researchers [Jensen, 2014;Ziegler et al, 2021] by providing a clear method of pre-and post-intervention evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the current paper indicates that the use of open-response questions and drawing with young children provides a helpful method of identifying changes in scientific knowledge before and after a cross-curricular workshop linking science and art. Following Ziegler et al [2021] we present the evaluation as a way of sharing learning with the science communication community. We found that the use of online comparative marking to rank children's responses allows a straight-forward method for data analysis which can be used by science communication and engagement project teams who may not have a background in qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dafür brauchen wir im Wissenschaftssystem mehr Reflexion darüber, was Wissenschaftskommunikation bei wem erreichen soll. Und es braucht mehr kritische Betrachtungen der aktuellen Praxis durch Forschung und Evaluation, 11)…”
Section: Die Zukunftunclassified
“…This moderate impact could be due to the lack of benchmarks on effective communication. There is virtually no access to evaluations of scientific communication, and there are virtually no success stories or examples of ineffective communication that would allow organisations to learn from the experience [45].…”
Section: The Need For Innovation Diffusionmentioning
confidence: 99%